A Design of Bang-Bang PLL in Low Jitter and Wide Pull-in Range - Xihong Chen; Qiang Liu; Denghua Hu (Institute of Advanced Engineering and Science, 2014)
As bang-bang PLL (BBPLL) could resume clock data rapidly, its application in clock data recovery has become increasingly abroad. Aiming at the contrary demand of lower jitter and wider pull-in range of BBPLL, the issue puts forth a method to choose the most appropriate gain of digitally controlled oscillator (DCO) to settle. A judged and modified model has been added to the 2nd order traditional BBPLL, which modified the gain of DCO dynamically by step forward method. Meanwhile it proposes pull-in jitter function (PJF) to judge the modified results. Then it takes a gradual comparison means to search the max PJF. It could be concluded from the simulations that the algorithm of the issue could get a compromise DCO gain in view of BBPLL’s jitter and pull-in range.